Introduction to a Phenomenology of Life - Barbaras, Renaud (Studies in Continental Thought Series., 2022)
Combining original interpretations and expert readings of philosophers such as Kant and Husserl and contemporary thinkers such as Bergson, Badiou, and Deleuze, Barbaras offers here a powerful and important contribution to phenomenology and continental thought.